The Effect of Perceived Usability and Algorithmic Personalization on Continuance Intention through Perceived Value on the Netflix Digital Subscription Platform - Jihan Alya Rahma Putri Irmawan; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Journal of Digital Business and Global Economy, 2025)
Through perceived value acting as a mediating variable, it attempts to examine the impact of perceived usability and algorithmic personalization on continuing intention across the Netflix digital subscription platform. 88 Netflix users participated in this instance, which takes a quantitative approach using the PLS-SEM method. According to the outcomes, perceived usability enhances perceived value but has no discernible tangible impact on continuing intention. On another aspect, both continuance intention and perceived value have been beneficially affected by algorithmic personalization. Furthermore, it has been proven that continuance intention is improved by perceived value. It implies that the role of perceived usability and algorithmic personalization on continuing intention on digital subscription platforms is mediated by perceived value.